Physiological and Reproductive Characteristics of Rabbit Bucks Fed Cassia tora Leaf Meal Diets in the Semi-Arid Zone - Chintem, A.M; Daudu, O.M.; Abdulrashid, M. (Nigerian Journal of Animal Science, 2023)
A total of 30, 18 weeks old rabbit bucks with an average weight of 1.5-2kg were allotted into five treatments consisting of six bucks each in a completely randomized design (CRD). The results of this study revealed higher (P<0.05) respiratory rate (175.59 and 167.77 brpm) in bucks fed 10 and 20% Cassia tora leaf meal diets. Rectal temperature (38.79-38.99oC) of the bucks fed Cassia tora leaf meal diets were higher (P<0.05) than other bucks. Average daily feed intake (73.6-84.75 g/d) and White blood cell count of rabbit bucks fed 5, 10 and 20% Cassia tora leaf meal diets were higher (P<0.05). Rabbit bucks fed Cassia tora leaf meal diets had 0% mortality while bucks fed control diet had 16.67% mortality. Packed cell volume of the rabbit bucks fed 0% Cassia tora leaf meal diets was higher (P<0.05); haemoglobin concentration, albumin and low density lipoprotein of the rabbit bucks fed 10% Cassia tora leaf meal diets was higher (P<0.05) than other bucks; Red blood cell count of the bucks fed 0% Cassia tora leaf meal diets was higher (P<0.05). Total proteins and triglycerides of rabbits bucks fed 0 and 5% Cassia tora leaf meal diets were higher (P<0.05). The serum antioxidant activities of catalase and superoxide dismutase of rabbit bucks fed 10, 15 and 20% dietary Cassia tora leaf meal diets were higher (P<0.05). Semen evaluation shows that semen color, semen pH, normal cells, free tail, coiled tail and detached head were statistically (P>0.05) similar in all treatments. Semen volume of rabbit bucks fed 0, 5, 15 and 20% Cassia tora leaf meal diets were higher (P<0.05). Reaction time, sperm concentration and motility of the rabbit bucks fed 20% Cassia tora leaf meal diets were higher (P<0.05) than other bucks. Percent live sperm of bucks fed 0 and 20% Cassia tora leaf meal diets were higher (P<0.05) than rabbit bucks fed 5, 10 and 15% Cassia tora leaf meal diets. The incidence of bent tail was higher (P<0.05) in bucks fed 5% Cassia tora leaf meal diet. In conclusion, the temperature humidity index values of this study indicate absence of heat stress both in the morning and afternoon period. Rectal temperatures of the bucks were within the normal range. Haematological and biochemical indices of all the rabbit bucks were within the normal physiologic range. Rabbits fed Cassia tora leaf meal diets had increased catalase and superoxide dismutase activities. Rabbit bucks fed 20% Cassia tora leaf meal diet had similar reaction time, semen volume, sperm concentration, motility and live sperm with the bucks on control, an indication that it can be fed to breeding bucks without any detrimental effect.